Extracellular water compartment in hemodialyzed patients with normal blood pressure and with hypertension - Małecka-Massalska, Teresa; Mądro, Elżbieta; Lupa, Krystyna; Załuska, Wojciech; Książek, Andrzej (Polish Journal of Public Health, 2010)
Introduction. Evaluation of hydration levels in dialyzed patients is an essential part of dialysis therapy. Bioimpedance is a valuable tool in the evaluation of the hydration level of the body in the dialyzed patient. Aim. The aim of this study was to examine the correlation between hydration values and parameters such as: • dialysis adequacy parameter, protein catabolism rate (PCR, Kt/V)• nutrition rate (albumin concentration, total protein concentration, creatinine concentration before haemodialysis) in haemodialyzed patients with normal blood pressure and with hypertension.Material and method. A single examination was carried out before haemodialysis with the use of the whole body bioimpedance for 51 dialyzed patients divided into two groups – the group of haemodialyzed patients with normal blood pressure (11 individuals: 5 females and 6 males) and the group of haemodialyzed patients with hypertension (40 individuals: 17 females and 23 males). In the correlation study statistically significant correlation was proven between: ECW and Kt/V (r = -0.80; p = 0.003), ICW and Kt/V (r = -0.60; p = 0.05) in haemodialyzed patients with normal arterial blood pressure (normotonics) before haemodialysis. Results. In the group of haemodialyzed hypertonics, significant correlation was shown between: ECW and Kt/V (r = -0.43; p = 0.006), ICW and total serum protein concentration (r = 0.41; p = 0.008), ICW and creatinine concentration before HD (r = 0.49; p = 0.001). In the group of haemodialyzed patients with normal arterial blood pressure and with hypertension before haemodialysis, statistically significant correlation was proven between: systolic pressure and ECW (r = 0.31; p = 0.03), systolic pressure and ECW/body weight before HD (r = 0.44; p = 0.001). Conclusions. The results of the study have shown the inverse proportional relation between ECW and Kt/V among hemodialyzed patients either with normal blood pressure or with hypertension.